A rapid hybridization-free LAMP–LFB assay for the clinical detection of Neisseria gonorrhoeae in urine specimens - Jutturong Ckumdee; Somchai Santiwatanakul; Rossaphorn Kittiyaowamarn; Thongchai Kaewphinit (Scientific Reports, 2026)
Abstract Neisseria gonorrhoeae remains a critical global public health challenge, particularly in regions where access to rapid molecular diagnostics is constrained. In this study, we developed and clinically validated a hybridization-free loop-mediated isothermal amplification-lateral flow biosensor (LAMP-LFB) assay for the rapid detection of N. gonorrhoeae in urine specimens. The hybridization-free format is achieved through dual-labeled LAMP primers, in which biotin and fluorescein isothiocyanate (FITC) labels are incorporated during primer synthesis, generating pre-labeled amplicons that are directly detected on a lateral flow strip without post-amplification hybridization or probe-based steps. In this pilot analytical evaluation, the LAMP–LFB assay showed a preliminary detection limit of 10 CFU/mL, with no cross-reactivity observed against non-target bacterial species. Clinical evaluation of 140 urine specimens, using the cobas CT/NG assay as the reference method, demonstrated 100% sensitivity (83/83; 95% CI: 95.6–100%) and 100% specificity (57/57; 95% CI: 93.7–100%). The assay was completed within approximately 65 min, including a 5-minute visual readout. The system operates in a closed-tube, one-step format in which FITC- and biotin-labeled amplicons generated during LAMP are detected directly within an integrated lateral flow biosensor device without opening the post-amplification tube, thereby reducing the risk of carryover contamination and supporting deployment in decentralized and point-of-care settings.